Răspuns :
Fie x-suma de bani
y=restul
z-noul rest
x-1/4x=y
y-1/6y=z
z-1/3*z-120=600
z-1/3*z=600+120
Amplificam z cu 3 ca sa aducem la acelasi numitor
(3z-z)/3=720
2z=720*3
2z=2160
z=2160/2=1080 lei
y-1/6*y=1080
6y-y/6=1080
5y=1080*6
5y=6480
y=6480/5
y=1296 lei
x-1/4*x=1296
3x/4=1296
3x=1296*4
3x=5184
x=5184/3
x=1728 lei
y=restul
z-noul rest
x-1/4x=y
y-1/6y=z
z-1/3*z-120=600
z-1/3*z=600+120
Amplificam z cu 3 ca sa aducem la acelasi numitor
(3z-z)/3=720
2z=720*3
2z=2160
z=2160/2=1080 lei
y-1/6*y=1080
6y-y/6=1080
5y=1080*6
5y=6480
y=6480/5
y=1296 lei
x-1/4*x=1296
3x/4=1296
3x=1296*4
3x=5184
x=5184/3
x=1728 lei
x-suma initiala
1/4 din x= 1/4 * x= x/4 -prima data
x-x/4= (4x-x)/4= 3x/4 -restul
1/6 din 3x/4= 1/6 * 3x/4= 1/2 *x/4= x/8 -a doua oara
3x/4- x/8= (6x-x)/8= 5x/8- noul rest
1/3 din 5x/8 +120 = 1/3 * 5x/8= 5x/24 +120 -a treia oara
5x/8 -5x/24 -120= (15x-5x-2880)/24= (10x-2880)/24 -noul nou rest
(10x-2880)/24=600
10x-2880=600*24
10x-2880=14400
10x=14400+2880
10x=17280
x=1728
1/4 din x= 1/4 * x= x/4 -prima data
x-x/4= (4x-x)/4= 3x/4 -restul
1/6 din 3x/4= 1/6 * 3x/4= 1/2 *x/4= x/8 -a doua oara
3x/4- x/8= (6x-x)/8= 5x/8- noul rest
1/3 din 5x/8 +120 = 1/3 * 5x/8= 5x/24 +120 -a treia oara
5x/8 -5x/24 -120= (15x-5x-2880)/24= (10x-2880)/24 -noul nou rest
(10x-2880)/24=600
10x-2880=600*24
10x-2880=14400
10x=14400+2880
10x=17280
x=1728